Labor and Capital on the African Copperbelt - Parpart, Jane L. (Temple University Press, 2018)
Labor and Capital on the African Copperbelt is an admirable introduction to social formation and class struggle in a historic phase of central African history and a history of labor on the Copperbelt. Beginning with their experiences in the Northern Rhodesian copper mines in the 1920s, black miners and their families gradually developed a sense of themselves as a class of workers. Their class consciousness led them to form associations and to strike against the copper companies in 1935 and 1940. However, there were also periods in the 1950s and '60s where the companies and the government effectively neutralized labor protest. Drawing on interviews and company archives, this is an unusually rich and complete study of the complex relations among labor, capital, and the state, and Parpart connects the experiences that began in the corporate environment of the mines with the eventual success of the movement for Zambia independence The interviews provide a look into the daily lives of the workers, the rhythms of trade union development, and the nature of the fit between unionism and nationalist politics.